Categorization of risk factors for distributed agile projects - Shrivastava, Suprika V.; Rathod, Urvashi (Information and software technology, 2015)
•Identification of DAD risk factors and the approaches for DAD risk management.•In depth exploration of practitioners’ experience and related research literature.•Categorization of identified DAD risk factors using constant comparison method.•DAD risk categories mapped to Leavitt’s model of organizational change.•Identified the conflict between distributed and agile development that cause risks. Organizations combine agile approach and Distributed Software Development (DSD) in order to develop better quality software solutions in lesser time and cost. It helps to reap the benefits of both agile and distributed development but pose significant challenges and risks. Relatively scanty evidence of research on the risks prevailing in distributed agile development (DAD) has motivated this study. This paper aims at creating a comprehensive set of risk factors that affect the performance of distributed agile development projects and identifies the risk management methods which are frequently used in practice for controlling those risks. The study is an exploration of practitioners’ experience using constant comparison method for analyzing in-depth interviews of thirteen practitioners and work documents of twenty-eight projects from thirteen different information technology (IT) organizations. The field experience was supported by extensive research literature on risk management in traditional, agile and distributed development. Analysis of qualitative data from interviews and project work documents resulted into categorization of forty-five DAD risk factors grouped under five core risk categories. The risk categories were mapped to Leavitt’s model of organizational change for facilitating the implementation of results in real world. The risk factors could be attributed to the conflicting properties of DSD and agile development. Besides that, some new risk factors have been experienced by practitioners and need further exploration as their understanding will help the practitioners to act on time. Organizations are adopting DAD for developing solutions that caters to the changing business needs, while utilizing the global talent. Conflicting properties of DSD and agile approach pose several risks for DAD. This study gives a comprehensive categorization of the risks faced by the practitioners in managing DAD projects and presents frequently used methods to reduce their impact. The work fills the yawning research void in this field.